O processamento da anáfora pronominal em crianças com transtorno de déficit de atenção e hiperatividade e em crianças disléxicas : um estudo através da análise dos movimentos oculares - Klein, ângela Inês (2013)
The general aim of this work was to analyze the reading comprehension process of texts with pronominal anaphora by children that have attention deficit hyperactivity disorder or dyslexia. The sample studied consisted of 75 children that speak German and attended from third to seventh grade. Three groups were organized: children with ADHD diagnosis or with dyslexia and children with no disorders, who read two texts of 80 words each. The eye movements of all participants were recorded and, to make sure they were reading with attention, two activities that tested reading comprehension were proposed. The specific objectives of this study were: 1) to test the necessary demand of time for reading comprehension of texts with pronominal anaphora in children that have attention deficit hyperactivity disorder and dyslexic children. 2) to examine the process of resolution of pronominal anaphora in children; 3) to verify the processing of pronominal anaphora in children that have attention deficit hyperactivity disorder and dyslexic children.All objectives proposed were achieved, leading to following conclusions: 1) children with disorders may have results as good as of the control group in reading comprehension tests, however, they need more time; 2) children with disorders carry out atypical eye movements both in fixation and in saccade; 3) the processing of pronominal anaphora in children happens the moment they see the pronoun and not in the following words; 4) children with disorders have difficulty to process the pronominal anaphora, especially dyslexic children